Experimental investigation of mechanical, acoustic and hybrid metamaterial designs for enhanced and multi-band electric motor noise dissipation. (15th November 2022) - Tian, Zhenhuan; Bennett, J.; Yang, J.; Lawrie, T.; Elmadih, W.; Bardalai, A.; Gerada, C.; Zhu, Jian; Chronopoulos, D.
Abstract: Acoustic metastructures exhibit an unprecedented ability to arbitrarily manipulate the properties of sound waves, including amplitude and phase modulation which has attracted much attention in both the academic and industrial communities. Design of metastructures has been extensively investigated for the purpose of the independent manipulation of acoustic and elastic waves. It is up to now unclear however if the optimal dissipation approach involves locally resonant structural elements, or locally resonant acoustic cavities or a hybrid mix of both noise abatement mechanisms. To study this problem, we investigate numerically and experimentally the noise reduction performance of acoustic and mechanically locally resonant structures and how they perform when integrated into the same application scenario. Taking the noise emission of an electric motor as the excitation regime for our study, the acoustic and mechanical metamaterial structures with respective C-shape and T-shaped resonators are judiciously designed to maximize noise dissipation within two targeted frequency bands where the motor noise peaks. A hybrid structure with a mix of both resonators is also designed. The results demonstrate that all three metastructure designs improved the noise attenuation performance with an additional sound insertion loss of up to 16 dB when compared to a flat wall structure of equivalent mass. The findings in this work demonstrate that significant noise attenuation can be obtained by incorporating these acoustic and mechanical meta-atoms into a wall architecture which may have great potential for real world applications such as surrounding electric motors which tend to emit monotonic and irritating noise. Highlights: We identify pronounced noise signatures for a typical electric motor. Metastructures are designed for damping noise within two targeted frequency bands. The mechanical resonance, acoustic resonance and a hybrid design for noise damping. Large-scalemetastructures are experimentally tested within an anechoic chamber.